Application of the health information system in the Health Center Niš - Milošević, Zoran; Jerkan, Milorad; Stojanović, Miodrag; Premović, Natalija; Milošević, Sanja; Ignjatović, Aleksandra; Andjelković Apostolović, Marija (Medical Word, 2020)
Medical informatics is the science that studies the creating, transmitting, processing and using information, data and knowledge to solve medical problems. It is medical technology due to participation in the process of formal medical decision making. The first step in the development of health information systems in Serbia is the adoption of a national “Strategy for the Development of the Information Society in the Republic of Serbia by 2020”.The aim of this paper is to consider the advantages of using information technologies in the process of health care provision in health care institutions in comparison to the previous, classical way of collecting, analyzing and interpreting data in the example of primary health care institutions.The methodology is a retrospective study of the presentation of implementation in information technologies on the example of the Health Center Niš for the period from 2004. to 2019. and presentation of the computer equipment status.The implementation of the health information system will enable: better and more efficient access to patient information, faster diagnostics, faster and more reliable selection of medicines, greater patient safety, more time for health care employees, better and more complete health-statistical reporting and faster transfer of biomedical knowledge. The introduction of a health information system will allow the creation of an electronic health record and electronic medical history.In 2011, the Health Center Niš became a user of the medical information system MEDIS.NET, which was realized in the Laboratory for Medical Informatics of the Faculty of Electronic Engineering in Niš. The Adult Health Service and the Child and School Health Services were the first to use electronic records.
Keywords: medical informatics, health information system, primary health care, secondary health care